A natural semantic metalanguage approach on the meaning of animal taboo names in the Acehnese culture - Maria Ulfa; Mulyadi Mulyadi; Mhd. Pujiono; Khairina Nasution (Studies in English Language and Education, 2024)
This paper utilizes the Natural Semantic Metalanguage Approach (NSM) to explore the meanings of animal-related taboo names among the Acehnese in Indonesia. Through qualitative interviews with 12 respondents from Langsa City and Peureulak District in East Aceh, the NSM approach reveals two categories of animal taboos. The first, the taboo of swearing, involves offensive language equating individuals with animals like bui (pig), ase (dog), paee (gecko), muruwa (monitor lizard), and lemo (cow). The second, the taboo of fear, rooted in cultural beliefs, deems certain animals sacred and prohibits mentioning their names in natural settings, including rimueng (tiger), gajah (elephant), buya (crocodile), badeuk (rhinoceros), uleue (snake), and tikh (rat). Acehnese use alternative names to show respect, reflecting a belief that respecting nature facilitates harmonious living. The semantic primitive meaning of animals taboo for swearing involves a substantive component, a substantive relational of a kind, and bad as an evaluator. Equating humans with these animals is prohibited when their names are used in the context of insulting others. The taboo of fear is attributed to the animals perceived holiness and sacredness, with the semantic primitive involving something kind and bad. Acehnese believe these animals possess mystical powers and can hear their names when being called, hence suggesting the use of alternative names for these animals is preferable.